MRI Guided Focused Ultrasound-Mediated Delivery of Therapeutic Cells to the Brain: A Review of the State-of-the-Art Methodology and Future Applications - Ahmed, Nabid; Gandhi, Dheeraj; Melhem, Elias R.; Frenkel, Victor (Frontiers in Neurology, 2021)
Stem cell and immune cell therapies are being investigated as a potential therapeutic modality for CNS disorders, performing functions such as targeted drug or growth factor delivery, tumor cell destruction, or inflammatory regulation. Despite promising preclinical studies, delivery routes for maximizing cell engraftment, such as stereotactic or intrathecal injection, are invasive and carry risks of hemorrhage and infection. Recent developments in MRI-guided focused ultrasound (MRgFUS) technology have significant implications for treating focal CNS pathologies including neurodegenerative, vascular and malignant processes. MRgFUS is currently employed in the clinic for treating essential tremor and Parkinson’s Disease by producing precise, incisionless, transcranial lesions. This noninvasive technology can also be modified for nondestructive applications to safely and transiently open the blood-brain barrier (BBB) to deliver a range of therapeutics, including cells. This review is meant to familiarize the neuro-interventionalist with this topic and discusses the use of MRgFUS for facilitating cellular delivery to the brain. A detailed and comprehensive description is provided on routes of cell administration, imaging strategies for targeting and tracking cellular delivery and engraftment, biophysical mechanisms of BBB enhanced permeability, supportive proof-of-concept studies, and potential for clinical translation.